The Effect of Discovery Learning Model on Student Learning Outcomes In Science Subjects In Elementery Schools - Purwasi, Esi; Idris, Muhamad; Budi Irawan, David (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to determine the effect of the Discovery Learning model on students' learning outcomes in the subject of Natural and Social Sciences (IPAS) at SDN 7 Rantau Bayur, Banyuasin Regency. The research used a True Experimental design with a Pretest-Posttest Control Group Design. The study involved two classes: the experimental class, which applied the Discovery Learning model, and the control class, which was taught using the lecture method. The results showed an increase in the average score from pretest to posttest in the experimental class, from 57.00 to 77.80. This improvement was greater than that of the control class, which only increased from 56.75 to 67.50. Statistical analysis using the Independent Samples t-test showed a significance value of 0.003 (<0.05), indicating that H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that the Discovery Learning model has a positive effect on students' learning outcomes in IPAS material.